New antimicrobial peptides against foodborne pathogens: From in silico design to experimental evidence. (15th November 2016) - Palmieri, Gianna; Balestrieri, Marco; Proroga, Yolande T.R.; Falcigno, Lucia; Facchiano, Angelo; Riccio, Alessia; Capuano, Federico; Marrone, Raffaele; Neglia, Gianluca; Anastasio, Aniello
Highlights: An innovative approach to design new antimicrobial peptides is proposed. Mitochondrial-targeting peptides (MTPs) could be effective as antimicrobial agents. Designed MTPs show bactericidal activity vs the foodborne pathogen L. monocitogenes . MTPs represent a new source of templates to project new food bio-preservatives. Abstract: Recently there has been growing interest in the discovery of new antimicrobial agents to increase safety and shelf-life of food products. Here, we developed an innovative approach by introducing the concept that mitochondrial targeting peptides (MTP) can interact and disrupt bacterial membranes, acting as antimicrobial agents. As proof-of-principle, we used a multidisciplinary strategy by combining in silico predictions, docking simulations and antimicrobial assays, to identify two peptides, MTP1 and MTP2, which were structurally and functionally characterized. Both compounds appeared effective against Listeria monocytogenes, one of the most important foodborne pathogens. Specifically, a significant bactericidal activity was evidenced with EC50 values of 16.8 ± 1.2 μM for MTP1 and 109 ± 7.0 μM for MTP2. Finally, NMR structure determinations suggested that MTP1 would be oriented into the membrane bilayer, while the molecular shape of MTP2 could indicate porin-mediated antimicrobial mechanisms, as predicted using molecular docking analysis. Therefore, MTPs represent alternative sources to design new potential bio-preservatives.